THE INTERACTION OF REGIONAL ECONOMIES OF RUSSIA - Z. Musaeva (Publishing House of the State University of Management, 2017)
The article is devoted to the consideration of specific features that are inherent in the regional economies of Russia, as well as the determination of the scientific and practical significance of this issue. Next, we propose ways to solve the difficulties caused by these aspects of the regional economy. The article defines the concept of «regional economy» and identifies the main directions of its activities. Particular attention is paid to identifying the significance of the regional economy for the country's economy as a whole and considering the specific features of regional economies, their shortcomings and ways of minimization.